Justifiability of remand detention provision in Syariah Criminal Procedure Enactment (2003): a case of Selangor - Saadan, Mohd Hilmi; Wan Muhammad, Ramizah (2017)
This paper discusses about the justifiability of including a provision similar in nature and intent with section 117 of the Criminal Procedure Code (Act 593) into the Syariah Criminal Procedure Enactment (2003) of Selangor. The provision is significant in terms of procedural laws which gives the power to the authorities to detain and interrogate the suspect, investigate the case and gather as much information as possible so that the question of whether the suspect should be charged or not can be dispensed judiciously. The absence of this provision in the Syariah Criminal Procedure Enactment has actually dampened the significance of any case and as a result the suspect is released from interrogation after the time limit is exhausted. Section 117 of the CPC provides power to the police officer to apply for an extension up to 7 days or 14 days depending on the nature of the offence being investigated. The author also highlighted the reasons as well as justifications for the need for such provision especially in cases related to Muslims’ creeds and the sanctity of the Islamic religion since these are delicate matters and need to be scrutinized and investigated thoroughly before one can be charged in the Syariah Court.